Managers' Job Satisfaction During the Covid-19 Pandemic: Is Nonlinear Management Satisfying? - Małgorzata ADAMSKA-CHUDZIŃSKA; Lech GÓRNIAK (Communications of International Proceedings, 2021)
Job satisfaction is a crucial determinant of maintaining organizational effectiveness. In the current highly complex reality of the Covid-19 pandemic, the ability to manage non-linearly appears to be a particularly desirable aspect of managerial satisfaction. The CAWI survey method was implemented to identify the impact of nonlinear management on job satisfaction, using the author's questionnaire and MOAQ-JSS job satisfaction subscale and correlation analysis, and multiple regression analysis. The study covered a group of 149 Polish managers. The research results indicate that the surveyed managers are characterized by high job satisfaction and quite good adaptation to nonlinear circumstances. A significant relationship was found between the selected parameters of absorption of nonlinearity and the satisfaction of selected groups of respondents, i.e., female managers, managers of large companies, and middle-level managers. The research revealed the complexity of the issues discussed and factors partially limiting the impact of nonlinear management on managers' satisfaction. The obtained results can be useful when developing the solutions increasing satisfaction in the field of nonlinear management.
Keywords: Job Satisfaction; Manager; Nonlinear Management; Covid-19 Pandemic.